Road Congestion Pricing in Singapore: 1975-2003 - PHANG, Sock-Yong (Institutional Knowledge at Singapore Management University, 2004)
Facing traffic congestion in the Central Business District and enormous demands on scarce land resources by the growing number of motor vehicles, Singapore, a small island city-state the size of Seattle, embarked on a bold decision to reduce road congestion by implementing the famous Area Licensing Scheme in 1975. This was a manual system of tolls for multiple entries into the Restricted Zone. While achieving the intended effect of cutting down on the volume of vehicular traffic in the Restricted Zone, the authors (and others) found that the problem of congestion had merely shifted in time and place. Many changes were implemented, including shoulder pricing (reduced tolls before and after the peak period) to even out traffic flows in 1994, and the Weekend Car Scheme (1991) and Off Peak Car Scheme (1994) to encourage people to use the roads during off-peak hours. The Road Pricing Scheme was introduced in 1995 on a congested highway to familiarize the public with linear passage tolls. In 1998, Singapore discarded the manual system of road pricing in favor of Electronic Road Pricing, which permitted the charging of tolls per entry, based on vehicle size, route taken, and time of the day. This article traces the rationale for the various measures and discusses the successes and shortcomings for the various measures over a twenty-eight year period from 1975 to 2003.